Cultivo de amapola en México y alternativas al paradigma prohibicionista (2022)
In 2007, the declaration of the war against drugs and drug trafficking in Mexico unleashed dynamics of violence unusually intense and frequent, leading to a human rights crisis in the country, which leads to rethinking the relationship between society and drugs from alternative approaches. It is in this context that this article discusses the issue of poppy cultivation in Mexico, first analyzing the prohibitionist paradigm of drugs and the regulatory alternatives. Subsequently, the measurement of poppy in Mexico is problematized and some of the estimated figures are presented, which is related to a state of the issue about regulatory approaches to poppy. It is concluded that the debate on poppy regulation in Mexico is recent, stems from various political actors and is necessary for the present and future of Mexican public security.